TEKNOLOGI PETERNAKAN TERPADU BERBASIS ENERGI BARU TERBARUKAN DI KABUPATEN TANGERANG - Rosiana Indrawati; Sri Haryanti Prasetiyowati; Primanda Kiky Widyaputra (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2021)
Tangerang Regency has the largest cattle farm in Banten Province. Animal husbandry business activities can have a positive impact, namely increasing community economic activities, as well as negative environmental impacts, namely livestock waste both solid and liquid waste. Partners in this activity are the Arafah Agro livestock business group and Barokah UMKM located in Pakulonan Barat Village, Kelapa Dua District, Tangerang Regency. So far, livestock waste management is only limited to being collected and then used for plant fertilizer. The technology to be implemented is a biogas reactor with a capacity of 12 m3, a chopper, a feed mixer, a solar powered water pump and a 500 liter water reservoir, and a PLTS with a capacity of 300 WP. The stages of its activities start from identifying the real conditions of partners related to the application of technology, designing and making technology systems, testing the technology systems that have been made, and conducting training and mentoring to partners in operating and utilizing technology that has been disseminated. The output of this activity is the use of cow biogascoture for cooking and lighting for cages, the installation of a solar powered water pump to suck water from the well into the reservoir, which can later be used for drinking and bathing cows and other stable operations, grass chopper and feed mixer. help provide high quality cow feed, thereby increasing cow productivity by up to 50%.